Problemática fiscal en la aplicación de la NIIF 16 a los contratos de arrendamiento de las empresas del sector aviación comercial en el Perú - Poma Ticlavilca, Jose Luis (2021)
IFRS 16 – Leases was made official in Peru through Resolution No. 062-2016-EF/30 (06/14/2016) issued by the Accounting Regulatory Council. This accounting standard, which replaces IAS 17 Leases, establishes the principles for the recognition, measurement, presentation and information that lessees must disclose about their leases, including those leases of right-of-use assets in a sublease. This rule is effective from January 1, 2019. Until 2018, IAS 17 provided that lessees recognize their financial leases in the Statement of Financial Position (ESF); On the other hand, operating leases were not part of the ESF, that is, they only affected the results of the period. However, IFRS 16 provides for the recognition of all leases (financial and operating) in the ESF. This is an important change for the financial statements of the companies because it implies recognizing an asset for the right of use for the present value of the leases, and liabilities linked to the total obligation for the lease. Now, depending on the industry to which this rule is applied, the recognition of a new asset may be convenient from a financial perspective, this, due to the fact that the solvency and profitability indicators are measured based on the assets (e.g. the ROA). On the other hand, the recognition of the liability for the lease could generate an incorrect analysis of the indebtedness indicators, among others. Now, we have treated in a general way the main changes that the transition from IAS 17 to IFRS 16 implies, however, it is not yet possible to carry out the analysis of the tax effects of said changes, this is because the Income Tax Law Rent has not changed. Therefore, it is important to analyze the tax effects that the application of this new accounting standard generates for companies. The main question to be addressed is whether this rule will change the way companies determine their taxes. For this, we will rely on the doctrine and pronouncements of the Tax Authorities and Courts.